2021
DOI: 10.1108/imds-11-2020-0631
|View full text |Cite
|
Sign up to set email alerts
|

Exploring donor's intention in charitable crowdfunding: intrinsic and extrinsic motivations

Abstract: PurposeThis study adopts self-determination theory and stimulus-organism-response framework to develop a model that explores the motivations of such donors by considering their self-determination needs and extrinsic and intrinsic motivations.Design/methodology/approachBased on online survey data collected from 436 crowdfunding donors in China, this study follows a structural equation modeling analysis to test hypotheses.FindingsThe results indicate that perceived ease of use, perceived self-efficacy and social… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
38
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 46 publications
(42 citation statements)
references
References 60 publications
(113 reference statements)
3
38
0
1
Order By: Relevance
“…SDT has gained importance in crowdsourcing platforms (Flostrand et al, 2019 ; Zhao & Zhu, 2012a , 2012b ) and reward-based crowdfunding applications (Bretschneider & Leimeister, 2017 ); however, the application of SDT in the domain of DBC is scarce. Based on SDT, (Chen et al ( 2021 ) pointed out that intrinsically motivated supporters donate to a cause out of self-pleasure and enjoyment. Donating on charitable crowdfunding platforms provides internal satisfaction and fulfillment to donors (Bagheri et al, 2019 ; Cox et al, 2018 ), and DBC platforms also provide a sense of relatedness to them as fundraisers communicate on these platforms (Wang et al, 2019 ).…”
Section: Theoretical Underpinningmentioning
confidence: 99%
See 1 more Smart Citation
“…SDT has gained importance in crowdsourcing platforms (Flostrand et al, 2019 ; Zhao & Zhu, 2012a , 2012b ) and reward-based crowdfunding applications (Bretschneider & Leimeister, 2017 ); however, the application of SDT in the domain of DBC is scarce. Based on SDT, (Chen et al ( 2021 ) pointed out that intrinsically motivated supporters donate to a cause out of self-pleasure and enjoyment. Donating on charitable crowdfunding platforms provides internal satisfaction and fulfillment to donors (Bagheri et al, 2019 ; Cox et al, 2018 ), and DBC platforms also provide a sense of relatedness to them as fundraisers communicate on these platforms (Wang et al, 2019 ).…”
Section: Theoretical Underpinningmentioning
confidence: 99%
“…In the context of the scarce literature exploring this last dimension (i.e., the perspective of donors), we argue that it is important to explore the reasons and situations that explain the donors’ donation behavior. Kim et al ( 2021 ) assert that donors and their decisions to donate are based on various dimensions such as their choices, the cause, the relatability to the cause, their experience, their trust in the donation channel, the kind of appeal, and many more (Chen et al, 2021 ; Burtch et al, 2013 ); however, scant research studies have focused on the repeated donation behavior of these donors.…”
Section: Introductionmentioning
confidence: 99%
“…In other words, the substitution models of subsequent investors' herding behavior will dominate when prior funding levels are too high. One reason for this is that, while supporting donation-based crowdfunding projects involves prosocial motivation (Chen et al, 2021), research also indicates prosocial psychology can impact investors in reward-based crowdfunding (Calic and Shevchenko, 2020). Projects with higher funding levels are more likely to be successful, meaning they will no longer need superfluous financial support to meet their funding goals.…”
Section: Hypothesis Development 31 Effect Of Prior Funding Performancementioning
confidence: 99%
“…In addition, Zhang et al examined the helpfulness votes of Amazon commodity reviews and found that the length of comments has a significant impact on their persuasion ability, i.e., consumers may be more likely to recognize such comments and cast useful votes ( Zhang et al, 2010 ). Many studies on transactional communities also show that the length of comments has a positive impact on perceived information helpfulness ( Huang et al, 2015 ; Chen et al, 2021 ). For complex mental health information, longer content is more usually more systematic and standardized, which normally contains the responders’ detailed and rational analysis of mental status of the help-seekers, thus other visitors are more likely to cast a higher helpfulness vote after reading.…”
Section: Theoretical Background and Hypotheses Developmentmentioning
confidence: 99%
“…In the existing literature, scholars have explored the influential factors affecting online information helpfulness using various lenses and have mainly utilized two perspectives ( Racherla and Friske, 2012 ): information source (i.e., individual characteristics of the information providers), information quality (i.e., the content of the information) ( Chen et al, 2021 ). The majority of studies based on information sources in online comment communities find that reviewers own factors have a direct positive impact on the perceived helpfulness of comments ( Qigeng et al, 2017 ).…”
Section: Introductionmentioning
confidence: 99%